Anti‐Black Racism and Power: Centering Black Scholars to Achieve Health Equity. (26th April 2022) - Best, Alicia L.
Abstract: In health equity research, anti‐Black racism and power imbalances manifest at every phase of the research process and contribute to the marginalization and exclusion of Black scholars. This essay highlights how power operates as a central component of anti‐Black racism, and I describe the importance of centering Black scholars in funding, conducting, and implementing health equity research. Interdisciplinary collaboration between the fields of bioethics, public health ethics, and health equity could generate dialogue and develop recommendations to help balance power dynamics, address anti‐Black racism, and, ultimately, make meaningful progress toward health equity.